Glosa do wyroku Sądu Najwyższego z 19 kwietnia 2012 r., IV CSK 459/11, OSNC 2012/10/122 “Legitymacja do wytoczenia powództwa o ustalenie bezskuteczności uznania ojcostwa (art. 78 § 1 k.r.o.) przysługuje także mężczyźnie, który uznał ojcostwo, wiedząc, że nie jest biologicznym ojcem dziecka” - Ogrodnik-Kalita, Agnieszka (Przegląd Prawno-Ekonomiczny, 2014)
Streszczenie dostępne wyłącznie w języku angielskim: The subject of the gloss is the Supreme Court’s judgement of 19 April 2012 (IV CSK 459/11). The judgement focuses on the problem of bringing legal action to esstablish the ineffectiveness of recognition of paternity by the man, who knew that he was not child’ s father when he recognized paternity. According to the Supreme Court, the man who knew as well as the one who did not know that he did not father the child, may bring legal action. In the Author’s view, the Supreme Court is right, taking into account the nature of the recognition of paternity.